2006
DOI: 10.1007/s00109-006-0065-1
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presentation in autoimmunity and CNS inflammation: how T lymphocytes recognize the brain

Abstract: The central nervous system (CNS) is traditionally viewed as an immune privileged site in which overzealous immune cells are prevented from doing irreparable damage. It was believed that immune responses occurring within the CNS could potentially do more damage than the initial pathogenic insult itself. However, virtually every aspect of CNS tissue damage, including degeneration, tumors, infection, and of course autoimmunity, involves a significant cellular inflammatory component. While the blood-brain barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
169
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 139 publications
0
169
0
Order By: Relevance
“…Following systemic immunization with myelin antigens like MOG, naïve T cells interact with APC within secondary lymphoid organs, leading to activation and expansion of neuroantigen-specific T cells [46]. Before invading the CNS parenchyma, MOG-specific T cells need to reencounter their cognate antigen in the periphery to be fully activated [35]. Candidates recently proposed to mediate antigen presentation during EAE are dendritic cells [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following systemic immunization with myelin antigens like MOG, naïve T cells interact with APC within secondary lymphoid organs, leading to activation and expansion of neuroantigen-specific T cells [46]. Before invading the CNS parenchyma, MOG-specific T cells need to reencounter their cognate antigen in the periphery to be fully activated [35]. Candidates recently proposed to mediate antigen presentation during EAE are dendritic cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…Following systemic immunization with MOG, encephalitogenic T cells primed in the periphery migrate to the CNS where they reencounter their cognate antigen and develop inflammatory infiltrates (reviewed in [35]). To address the amount of immune cell infiltration into the CNS at the peak of disease, we used flow cytometry to quantify the abundance of total CNS infiltrating cells in the inflamed brains and spinal cords.…”
Section: T Cells Are Significantly Increased In the Cnsmentioning
confidence: 99%
“…In addition to their role in innate immunity, macrophages can contribute to adaptive immune responses through the presentation of antigenic peptides on MHC molecules (Becher et al 2006;Hume 2008). Flow cytometric analysis revealed that only a minority of LPS-activated BMM expresses MHC class II molecules and that the costimulatory molecules CD80 and CD86 are expressed at very low levels (Fig.…”
Section: Hgf Induces Proliferation Of Lps-activated Macrophages But Dmentioning
confidence: 99%
“…The main inflammatory effector cells are CD4 + T cells (Bynoe et al 2007;Platten and Steinman 2005;Wekerle 2008), which are initially primed in peripheral lymphoid tissues mainly by antigen presenting dendritic cells (DCs). An additional local T cell re-activation phase mediated by CNSassociated antigen presenting cells (APCs), such as microglia, macrophages and DCs, is thought to be essential for the disease to develop (Becher et al 2006;Platten and Steinman 2005). In addition activated microglia and CNS-infiltrating peripheral macrophages contribute directly to CNS damage through the production of proinflammatory cytokines, matrix metalloproteinases, glutamate, and free radicals (Hemmer et al 2002;Piani et al 1991;Piani et al 1992;Platten and Steinman 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Every step in this sequence of events, i.e. crossing of the blood brain barrier, re-activation in the perivascular compartment, infiltration into the CNS parenchyma, immune cell/target cell interaction within the CNS parenchyma, lesion development, and resolution of inflammation as well as tissue repair have all been extensively studied in EAE [18,19]. During the last 30 years, EAE has become one of the most successful animal models in preclinical research and basic T cell immunology.…”
Section: Introductionmentioning
confidence: 99%